High resolution IgH repertoire analysis reveals fetal liver as the likely origin of life-long, innate B lymphopoiesis in humans - Roy, A; Bystry, V; Bohn, G; Goudevenou, K; Reigl, T; Papaioannou, M; Krejci, A; O'Byrne, S; Chaidos, A; Grioni, A; Darzentas, N; Roberts, I; et al. (Elsevier, 2017)
The ontogeny of the natural, public IgM repertoire remains incompletely explored. Here, high-resolution immunogenetic analysis of B cells from (unrelated) fetal, child, and adult samples, shows that although fetal liver (FL) and bone marrow (FBM) IgM repertoires are equally diversified, FL is the main source of IgM natural immunity during the 2nd trimester. Strikingly, 0.25% of all prenatal clonotypes, comprising 18.7% of the expressed repertoire, are shared with the postnatal samples, consistent with persisting fetal IgM+ B cells being a source of natural IgM repertoire in adult life. Further, the origins of specific stereotypic IgM+ B cell receptors associated with chronic lymphocytic leukemia, can be traced back to fetal B cell lymphopoiesis, suggesting that persisting fetal B cells can be subject to malignant transformation late in life. Overall, these novel data provide unique insights into the ontogeny of physiological and malignant B lymphopoiesis that spans the human lifetime.